Why do experts disagree? The role of conflict topics and epistemic perspectives in conflict explanations. (December 2017) - Thomm, Eva; Barzilai, Sarit; Bromme, Rainer
Abstract: The present study examined the role of conflict topics and individual differences in epistemic perspectives (absolutism, multiplism, and evaluativism) in students' explanations of expert conflicts. University students ( N = 184) completed an epistemic thinking assessment and a conflict explanation assessment regarding two controversies in biology and history. Additionally, thirty students were interviewed and provided detailed conflict explanations that were used to interpret and extend the quantitative results. In the biology problem, conflicts were predominantly attributed to topic complexity and to research methods. In the history problem, conflicts were also predominantly attributed to topic complexity, but also to researchers' personal backgrounds and motivations. Epistemic perspectives were related to specific conflict explanations, suggesting that these perspectives have a role beyond topic differences. Thus, both conflict topics and epistemic perspectives shape lay explanations of experts' conflicts. The findings highlight differences in students' interpretations of the roles experts play in knowledge construction. Highlights: University students endorsed different conflict explanations in biology and history. In biology, knowledge-related explanations were predominantly endorsed. In history, both knowledge- and researcher-related explanations were endorsed. Conflict explanations were associated with individuals' epistemic perspectives. Experts' role in knowledge construction was interpreted differently across contexts.